Towards a structure of the HIV-1 envelope glycoprotein gp120: an immunochemical approach. - Moore, J; Jameson, B; Sattentau, Q; Willey, R; Sodroski, J (1993)
The HIV-1 surface glycoprotein gp120 binds CD4 in the initial state of virus-cell fusion. The extensive glycosylation of gp120 has thus far precluded definition of its structure by crystallographic methods. As an initial approach to a gp120 structure, the surface topology was mapped using antibodies. First, the regions of gp120 that are accessible on the surface of the native molecule, and those that are internal but exposed after denaturation, are identified. Second, epitopes for antibodies that recognize complex surface structures comprising segments of different domains are identified. Third, we define how mutations in one domain of gp120 influence the binding of antibodies to defined epitopes on other domains. These latter approaches enable us to start to understand the inter-domain interactions that contribute to the overall structure of the gp120 molecule. Information from these studies is being used to model the structures of individual gp120 domains, and the way in which these interact in the folded protein.